2011
DOI: 10.1603/ec10216
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Wood Hardness and Secondary Compounds on Feeding Preference of Odontotermes formosanus (Isoptera: Termitidae)

Abstract: Odontotermes formosanus (Shiraki) (Isoptera: Termitidae) is one of the most destructive plant pests in China, which control relies mainly on baits strategies. Baits made from the wood of eight different tree species were used to study the feeding preference of this termite, and conversely wood protection strategies of the tree species. Three bait types were used to identify wood protection strategies: solid wood (physical and chemical protection), crude flour (chemical protection) made from ground wood, and ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 22 publications
0
12
0
1
Order By: Relevance
“…In a recent study with the blackwinged termite, Kasseney et al [12] found that solid wood consumption was inversely correlated with wood density and positively correlated with glucose concentration. Although camphor had moderately dense wood, it also had the greatest concentration of glucose among the wood species tested [12]. Perhaps feeding on bark allows these termites to avoid the dense solid wood while feeding on more glucose-rich cellulose.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In a recent study with the blackwinged termite, Kasseney et al [12] found that solid wood consumption was inversely correlated with wood density and positively correlated with glucose concentration. Although camphor had moderately dense wood, it also had the greatest concentration of glucose among the wood species tested [12]. Perhaps feeding on bark allows these termites to avoid the dense solid wood while feeding on more glucose-rich cellulose.…”
Section: Discussionmentioning
confidence: 99%
“…Laboratory feeding preference studies that compare black-wing termite feeding on camphor and fir are clearly indicated. Many factors including wood density, presence of protective compounds, and concentration of glucose affect black-winged termite feeding preferences [12]. In a recent study with the blackwinged termite, Kasseney et al [12] found that solid wood consumption was inversely correlated with wood density and positively correlated with glucose concentration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Their high content may decrease surface reaction of the lignocellulosic materials, besides blocking adhesive entering by superficial concentration in high temperatures used during pressing (FRIHART; HUNT, 2010). However, it should be mentioned that besides quantitative variations, extractives also vary in chemical nature and depend on species and environmental conditions (BALLESTEROS et al, 2011;BRÉMAUD et al, 2011;KASSENEY et al, 2011). Therefore, their effect on particleboard production may also vary.…”
Section: Raw Materials Characterizationmentioning
confidence: 99%